Tribendimidine and albendazole for treating soil-transmitted helminths, Strongyloides stercoralis and Taenia spp.: open-label randomized trial. - Peter Steinmann; Xiao-Nong Zhou; Zun-Wei Du; Jin-Yong Jiang; Shu-Hua Xiao; Zhong-Xing Wu; Hui Zhou; Jürg Utzinger (Public Library of Science (PLoS), 2008)
BACKGROUND: Tribendimidine is an anthelminthic drug with a broad spectrum of activity. In 2004 the drug was approved by Chinese authorities for human use. The efficacy of tribendimidine against soil-transmitted helminths (Ascaris lumbricoides, hookworm, and Trichuris trichiura) has been established, and new laboratory investigations point to activity against cestodes and Strongyloides ratti. METHODOLOGY/PRINCIPAL FINDINGS: In an open-label randomized trial, the safety and efficacy of a single oral dose of albendazole or tribendimidine (both drugs administered at 200 mg for 5- to 14-year-old children, and 400 mg for individuals > or = 15 years) against soil-transmitted helminths, Strongyloides stercoralis, and Taenia spp. were assessed in a village in Yunnan province, People's Republic of China. The analysis was on a per-protocol basis and the trial is registered with controlled-trials.com (number ISRCTN01779485). Both albendazole and tribendimidine were highly efficacious against A. lumbricoides and, moderately, against hookworm. The efficacy against T. trichiura was low. Among 57 individuals who received tribendimidine, the prevalence of S. stercoralis was reduced from 19.3% to 8.8% (observed cure rate 54.5%, p = 0.107), and that of Taenia spp. from 26.3% to 8.8% (observed cure rate 66.7%, p = 0.014). Similar prevalence reductions were noted among the 66 albendazole recipients. Taking into account "new" infections discovered at treatment evaluation, which were most likely missed pre-treatment due to the lack of sensitivity of available diagnostic approaches, the difference between the drug-specific net Taenia spp. cure rates was highly significant in favor of tribendimidine (p = 0.001). No significant adverse events of either drug were observed. CONCLUSIONS/SIGNIFICANCE: Our results suggest that single-dose oral tribendimidine can be employed in settings with extensive intestinal polyparasitism, and its efficacy against A. lumbricoides and hookworm was confirmed. The promising results obtained with tribendimidine against S. stercoralis and Taenia spp. warrant further investigations. In a next step, multiple-dose schedules should be evaluated.